Tahap kecerdasan emosi guru-guru pendidikan khas integrasi di Sekolah Rendah daerah Batu Pahat, Johor - Mohd. Sajat, Nofazilah (2014)
Emotional intelligence has become one of the most important determinants to measure success in the life of a teacher’s career. Therefore, a study was conducted to investigate the emotional intelligence of special education teachers in primary schools in Batu Pahat, Johore. This study were involving the five constructs of emotional intelligence: self-control, self-regulation, self-motivation, emotion management social and social skills. This study aimed to look at differences in emotional intelligence of special education teachers based on demographic factors and also the relationship between the level of emotional intelligence and challenging faced by special education teachers. The findings were analyzed using descriptive and inferential statistics. The findings showed that the level of emotional intelligence of special education teachers are at a high levels (mean = 3:98). This study also found that there was no significant differences in emotional intelligence based on age, length of service, professional qualification and courses in special education-related services. The study also showed that there were no significant correlation between the level of emotional intelligence and challenging levels. Overall, the findings from this study would be able to guide the special education teachers to improve the quality of themself, career and also student to enhance the quality of special education children in primary schools base on Philosophy of Education. Therefore, the researcher recommends a study such as this needs to be extended in each province or state that teachers have enhanced competencies. At the same time, the courses related to emotional management are particularly important as a resource for teachers to improve emotional intelligence.